Project Activities in the Process of Teaching Foreign Students - PANOVA, ELENA PAVLOVNA; FILIMONOVA, NATALIA YURYEVNA; BOCHARNIKOVA, NATALYA VICTOROVNA; DAVYDOVA, MARINA LEONIDOVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Foreign students who are trained in a country other than their own, face psychophysiological, educational, linguistic, didactic, sociocultural and other difficulties. To solve these problems, interactive forms of teaching are offered, in particular, the use of innovative technology, which is project-oriented student teaching. The study proposes a number of projects that foreign students could create in the first year of learning the russian language. The research projects proposed in the article have been tested at the Moscow Polytechnic University and at the Volgograd State Technical University.RESUMEN Los estudiantes extranjeros que se forman en un país distinto al de ellos, enfrentan dificultades psicofisiológicas, educativas, lingüísticas, didácticas, socioculturales y de otro tipo. Para resolver estos problemas, se ofrecen formas interactivas de enseñanza, en particular, el uso de tecnología innovadora, lo cual es la enseñanza estudiantil orientada a proyectos. El estudio propone una serie de proyectos que los estudiantes extranjeros podrían crear en el primer año de aprendizaje del idioma ruso. Los proyectos de investigación propuestos en el artículo han sido probados en la Universidad Politécnica de Moscú y en la Universidad Técnica del Estado de Volgogrado.